Cafeeiros podados fertirrigados com diferentes níveis de adubação - Souza, Victor Hugo Silva (2021)
The cultivation of coffee is of great importance on the national and international scene, with Brazil being the world's largest producer and exporter of this commodity. One of the key factors for achieving high yields is the adequate supply of nutrients, especially after drastic pruning. The objective was to establish a fertilization recommendation for fertigated coffee, in the fourth and fifth years after reception, by evaluating growth, yield (at harvest) and yields, in addition to evaluating changes in the anatomy and physiology of fertilized plants at different levels of N, P and K. Two experiments were carried out in Lavras - MG, in the Coffee Growing Sector of the Department of Agriculture of the Federal University of Lavras (UFLA). The crops were implemented in March 2010 and conducted with different levels of fertilization (fertirrigation), and in experiment 1, the levels of fertilization were varied since the implementation of the crop, and in experiment 2, the levels varied after the first year of formation. The seedlings used were of the cultivar Topázio MG-1190. Each experiment had 6 levels of fertilization (10%, 40%, 70%, 100%, 130% and 160%) of the standard recommended fertilization for rainfed coffee growing. In 2015, the plants were subjected to pruning of the “low vine, no lung” type, and evaluated for morphology, physiology and anatomy (2019/2020). The design used in the experiments was randomized blocks in a factorial scheme with split plots over time, with three replications, being a 6x2 factorial (six levels of fertilization and two harvests). Doses of N, P and K above 100% of the standard fertilization provided better growth of fertigated coffee trees, and in crops planted with fertilization levels below the recommended, their growth was compromised even up to the fourth and fifth years after receiving (10 years after implantation). Higher yields after reception are achieved in fertigated coffee trees, in plantations with fertilization levels close to those recommended and fertilized with at least 100% of the standard production fertilization, reaching productivity of up to 93.05 scs. ha-1. For the fertilization of fertigated crops in the fourth and fifth years after reception, with yields of around 93.05 scs. ha-1, at least 54.0 g is required. p1-1 N (450 kg.ha-1 N); 4.0 g. p1-1 P2O5 (33.3 kg.ha-1 P2O5); and 20.0 g. p1-1 K2O (166.7 kg.ha-1 K2O). In fertigated coffee plants with fertilization levels of 110% of the standard fertilization since the implementation of the crop, it is possible to obtain the yield in the fourth and/or fifth years after receiving 498.14 liters of coffee at the time of harvest, necessary for obtain a 60kg bag of processed coffee, while in conditions of nutritional deficiency 701.99 L may be needed. sc-1. Lower values of equatorial diameters and higher values of DP/DE found in the leaves of plants with higher levels of fertilization (100, 130 and 160%).